Paleontologists and archaeologists - Owen, Ruth, 1967- (New York : PowerKids Press, 2014)
An illustrated introduction to the careers of paleontologists and archaeologists, with examples of activities outside the laboratory.
Includes bibliographical references (p. 32) and index.
7.6
3-6
Keywords: Paleontologists -- Juvenile literature; Archaeologists -- Juvenile literature; Paleontology -- Vocational guidance -- Juvenile literature; Archaeology -- Vocational guidance -- Juvenile literature; Paleontologists; Archaeologists; Paleontology -- Vocational guidance; Archaeology -- Vocational guidance; Vocational guidance; Paleontologists; Archeologists; Paleontology -- Vocational guidance; Archeology -- Vocational guidance; Vocational guidance; Paleontologists -- Biography; Archaeologists; Hazardous occupations